Relationship Between Parenting Styles and Adaptive Behavior of Children in Telkom Kindergarten Makassar - Surganingsih, Muqimah; Hasmawaty, Hasmawaty; Intisari, Intisari; Islami, A. Nur Maharani (Universitas Negeri Makassar, 2024)
This study aims to identify parenting styles applied by parents to early childhood in Telkom Makassar Kindergarten and analyze the relationship between democratic, authoritarian, and permissive parenting styles with four main aspects of adaptive behavior in children: communication skills, daily life skills, socialization abilities, and motor skills. Using a quantitative approach with a correlational design, the study involved 40 children selected through proportional random sampling. Data were collected using validated and reliable questionnaires. The findings reveal that democratic parenting has the most positive impact on the development of all dimensions of adaptive behavior. Meanwhile, authoritarian and permissive parenting styles showed varying effects on specific dimensions. The study also found that a combination of parenting styles yields more optimal outcomes compared to the exclusive application of a single style. These findings highlight the importance of flexible and culturally sensitive parenting approaches to support holistic child development. This research provides theoretical and practical contributions to designing adaptive parenting strategies that promote the growth of early childhood development.